2019
DOI: 10.5423/ppj.oa.06.2019.0168
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nivalenol-Producing Fusarium asiaticum That Causes Cereal Head Blight in Korea

Abstract: Fusarium asiaticum of the F. graminearum species complex causes head blight in small-grain cereals. The nivalenol (NIV) chemotypes of F. asiaticum is more common than the deoxynivalenol (DON) chemotypes of F. asiaticum or F. graminearum in Korea. To understand the prevalence of F. asiaticum-NIV in Korean cereals, we characterized the biological traits of 80 cereal isolates of F. asiaticum producing NIV or 3-acetyl-deoxynivalenol (3-ADON), and 54 F. graminearum with 3-ADON or 15-acetyl-deoxynivalenol (15-ADON).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…asiaticum ‐NIV chemotype was more aggressive than the DON chemotypes, including the 3ADON and 15ADON chemotypes, in rice and less aggressive in wheat, while the DON chemotypes were more aggressive in wheat and less aggressive in rice. The results are consistent with those of recent pathogenicity tests in Korean and Chinese FGSC strains (Dong, Xu, et al, 2020; Dong, Zhang, et al, 2020; Jang et al, 2019). Further studies are necessary to reveal the mechanism underlying the increased aggressiveness of the F .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…asiaticum ‐NIV chemotype was more aggressive than the DON chemotypes, including the 3ADON and 15ADON chemotypes, in rice and less aggressive in wheat, while the DON chemotypes were more aggressive in wheat and less aggressive in rice. The results are consistent with those of recent pathogenicity tests in Korean and Chinese FGSC strains (Dong, Xu, et al, 2020; Dong, Zhang, et al, 2020; Jang et al, 2019). Further studies are necessary to reveal the mechanism underlying the increased aggressiveness of the F .…”
Section: Discussionsupporting
confidence: 92%
“…A limited number of reports have focused on the pathogenicity of FGSC strains in rice (Dong, Xu, et al, 2020; Dong, Zhang, et al, 2020; Goswami & Kistler, 2005; Jang et al, 2019; Lee et al, 2009). Some studies have shown that F .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this knowledge, information correlating mycotoxin contamination to the predominant species in Brazilian oats is still scarce [44][45][46][47][48][49][50][51]. In Europe, the high occurrence of F. poae in cereals is responsible for NIV contamination [37,52], while in Asia, NIV contamination is attributed to F. asiaticum [53,54]. In South America, NIV was found in wheat from Argentina and Brazil in lower frequency and levels than DON.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this knowledge, information correlating mycotoxin contamination to the predominant species in Brazilian oats is still scarce [43][44][45][46][47][48][49][50]. In Europe, the high occurrence of F. poae in cereals is responsible for NIV contamination [36,51]; while in Asia, NIV contamination is attributed to F. asiaticum [52,53].…”
Section: Discussionmentioning
confidence: 99%